Food resource partitioning among species of Astyanax (Characiformes: Characidae) in the Lower Iguaçu River and tributaries, Brazil - Pini,Suelen F. R. (2019)
ABSTRACT Resource partitioning allows for interspecific coexistence and is frequently reported for similar species. Here, we predicted the existence of resource partitioning among species of Astyanax that co-occur in the Low Iguaçu River and tributaries in Brazil. A total of 848 stomachs of five species of Astyanax were analyzed. Algae, terrestrial plant and fruit/seed were the most consumed resources. Astyanax bifasciatus and A. dissimilis had predominantly herbivorous diets, A. gymnodontus and A. lacustris were omnivorous, and A. minor was mainly algivorous. Permutational analysis of variance showed the species had different diets, and similarity percentage analysis indicated that fruit/seed and terrestrial plant contributed the most to this differentiation. A paired comparison indicated that the trophic breadth of A. gymnodontus differed from that of other species. The food overlap was low for 55% of Astyanax pairs. These results showed alignment with the niche theory, in which differentiation in the use of food resources facilitates the coexistence of species and minimizes competition. These adjustments to coexistence become relevant in the context of endemic species in a highly isolated basin under intense threat (dams, species introduction, deforestation, and pollution) as is the case for the Iguaçu River basin.